ANALISIS STRATEGI IMPLEMENTASI MEDIA SOSIAL (STUDI KASUS UKM “XYZ”) - Pandu Adi Cakranegara; Ety Susilowati (FIRM Journal of Management Studies, 2017)
Social media is is currently a trend for the company. It is free of charge and offer enormous benefit for the company. The purpose of this study is to find out how SME sector in implementing social media in the operational activities of its business? The research methodology used is case study with qualitative approach. The results of the study show In general, the SME sector has not optimally develop social media in promoting the company's business. The selection of social media tools is less precise. Instead some SMEs using all the plafform social media. Social media content is not yet optimal and contains information, videos or images that are not congested with company goals. Suggestions for SMEs are they can do the selection of models in accordance with their needs of such models. One example of the model is the model developed by Isra Garcia. In conclusion, social media options need to be suitable in with user needs.